If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 33 = 13x + -66 Reorder the terms: 33 + 6x = 13x + -66 Reorder the terms: 33 + 6x = -66 + 13x Solving 33 + 6x = -66 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 33 + 6x + -13x = -66 + 13x + -13x Combine like terms: 6x + -13x = -7x 33 + -7x = -66 + 13x + -13x Combine like terms: 13x + -13x = 0 33 + -7x = -66 + 0 33 + -7x = -66 Add '-33' to each side of the equation. 33 + -33 + -7x = -66 + -33 Combine like terms: 33 + -33 = 0 0 + -7x = -66 + -33 -7x = -66 + -33 Combine like terms: -66 + -33 = -99 -7x = -99 Divide each side by '-7'. x = 14.14285714 Simplifying x = 14.14285714
| 9x+38=17x | | -7(1-2x)=-77 | | 9(b-5)=4b-5 | | 6.2=c-3.1 | | m+2=0 | | 2x+17=9x-60 | | 6(10+4x)=252 | | 2(1x+5)=28 | | 116-7x=11x+18 | | 116-7x=11x+18x | | 5(3x+6)=120 | | 3x+32=5x+12 | | 14=4p-6 | | 5-7x=23-14x | | 4(k+5)=k+8 | | 9n^3+28n^2-32n= | | 2x-17=-3x+3 | | 5x+6=-99-10x | | 149-5x=6x+6 | | x-28=90 | | 132k+5=k-7 | | v^2=6v-5 | | 8a^3+27=0 | | 6+8x=55+x | | x-16=60 | | 5.5x-64=3.5x+14 | | 3x-3=10x-24 | | (5x+1)-(2x-6)=7 | | 5r=45 | | 5x+34=13x-46 | | 23x=96 | | 20x-16-13=8x+3 |